The Role of Geography Research in Supporting Sustainable Development in Ambon City, Indonesia: A Review - Manakane, Susan E; Latue, Philia Christi; Somae, Glendy; Rakuasa, Heinrich (Yayasan Sinergi Kawula Muda, 2023)
This study discusses the significant role of geographic research in supporting sustainable development efforts in Ambon City, Indonesia. Through the analysis of urban growth patterns, natural resource management, spatial planning, and identification of environmental and social impacts, geographic research provides insights that guide urban planners and decision-makers. This research. This research uses a descriptive qualitative approach. The type of research used is a literature study which is research that has been done before by collecting books, journals, magazines, and scientific papers that are related to how the utilization of geography research in the fields of disaster, regional and urban planning, health, tourism, agriculture and forestry and climate change is applied to realize an environmentally sound and sustainable Ambon City. The results show that Geography research plays an important role in supporting sustainable development in Ambon City, Indonesia, revealing that geography research is not just an analytical tool, but also a valuable guide for policy makers, urban planners, and communities in designing and implementing sustainable development. Through collaboration and application of research findings, Ambon City can grow into a city that not only develops economically, but also preserves the environment and the welfare of its people.